Lack of 13C-label incorporation suggests low turnover rates of thaumarchaeal intact polar tetraether lipids in sediments from the Iceland shelf - Lengger, Sabine; Lipsewers, Y.; De Haas, H.; Damste, J.; Schouten, S. (Copernicus GmbH, 2014)
Thaumarchaeota are amongst the most abundant microorganisms in aquatic environments, however, their metabolism in marine sediments is still debated. Labeling studies in marine sediments have previously been undertaken, but focused on complex organic carbon substrates which Thaumarchaeota have not yet been shown to take up. In this study, we investigated the activity of Thaumarchaeota in sediments by supplying different 13C-labeled substrates which have previously been shown to be incorporated into archaeal cells in water incubations and/or enrichment cultures.We determined the incorporation of 13C-label from bicarbonate, pyruvate, glucose and amino acids into thaumarchaeal intact polar lipid-glycerol dibiphytanyl glycerol tetraethers (IPL-GDGTs) during 4–6 day incubations of marine sediment cores from three sites on the Iceland shelf. Thaumarchaealintact polar lipids, in particular crenarchaeol, were detected at all stations and concentrations remained constant or decreased slightly upon incubation. No 13C incorporation in any IPL-GDGT was observed at stations 2 (clay-rich sediment) and 3 (organic-rich sediment). In bacterial/eukaryoticIPL-derived fatty acids at station 3, contrastingly, a large uptake of 13C label (up to + 80‰ ) was found. 13C was also respired during the experiment as shown by a substantial increase in the 13C content of the dissolved inorganic carbon. In IPL-GDGTs recovered from the sandy sediments at station 1, however, some enrichment in 13C (1–4‰ ) was detected after incubation with icarbonate and pyruvate.The low incorporation rates suggest a low activity of Thaumarchaeota in marine sediments and/or a low turnover rate of thaumarchaeal IPL-GDGTs due to their low degradationrates. Cell numbers and activity of sedimentary Thaumarchaeota based on IPL-GDGT measurements may thus have previously been overestimated.